(untitled) (Південний архів (історичні науки), 2023)
The purpose of the study is to characterize the process of teacher training in the Mykolaiv region in the 20s and 30s of the twentieth century, which mainly took place on the basis of the Teachers’ Institute established in 1913. The article will trace the changes that have taken place in the higher education institution over the decades and their impact on the process of teacher training, in particular, the reform of the teacher’s institute into the Institute of Public Education, the emergence of the first faculties and departments; the complexity of the process of training highly qualified specialists at the initial stage of formation, and then the strengthening of the totalitarian political regime. Methods: the systematic-functional method was used to identify general trends in teacher training in Soviet times, the historical-logical method, which allowed to trace the transformations in the process of training of specialists – teachers, traditional methods of cognition – theoretical analysis of literature, periodicals, as well as analysis, synthesis, systematization and interpretation of the data obtained. Results. The study examines the main stages of development of the main center of teacher training in Mykolaiv region and analyzes the main trends in state policy on teacher education. Conclusions. The studied sources and literature give grounds to say that the process of training pedagogical personnel in the period under study, albeit with considerable difficulty, continued, which had a positive effect on reducing the level of illiteracy among the population, improving the efficiency of work in the educational sector through the acquisition of a system of knowledge and the education of a generation of young people who had to work to overcome the country’s crisis and build society. A further in-depth consideration of this issue will make it possible to see the transformations that took place in this process, taking into account the changes inherent in state policy and the development of society at that time.